Reassessing the Expiatory Sacrifice for Hajj Tamattuʿ in Indonesia: A Qur’anic Exegesis and Socio-Legal Perspective on Contemporary Practices - Aswadi, Aswadi; Yusuf, M.; Jannah, Raudlotul; Tawwabuddin, Tawwabuddin; Ezzerouali, Souad (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Scholarly discourse on the permissibility and governance of expiatory sacrifice (dām) for ḥajj tamattuʿ in Indonesia continues amid rapidly evolving social and regulatory contexts. Existing studies are largely dominated by normative fiqh arguments and administrative policy considerations, while integrated analyses combining contextual Qur’anic exegesis, socio-legal perspectives, and maqāṣid al-sharīʿah remain limited. Addressing this gap, this study critically reassesses the coherence between Qur’anic norms, evolving interpretive frameworks, and contemporary policy implementation concerning dām for ḥajj tamattuʿ. This study employs a qualitative, library-based approach by analyzing key Qur’anic verses on ḥajj tamattuʿ through Abdullah Saeed’s contextualist interpretive framework and evaluating them using maqāṣid al-sharīʿah as a tool of critical legal reasoning. The normative findings are then examined in relation to socio-legal realities, including fatwas, state regulations, and institutional practices governing ḥajj administration in Indonesia and Saudi Arabia. The findings indicate that the obligation of dām for ḥajj tamattuʿ is not intrinsically confined to the Haram area but is context-dependent in terms of location, timing, and distribution, provided that its core spiritual objectives and public welfare considerations are fulfilled. Consequently, this study argues that cross-border regulatory coordination constitutes a normative implication of the dynamic relationship between Qur’anic injunctions, ritual practice, and contemporary ḥajj governance.